Biotratamento de sacolas plásticas de supermercado - Passolongo, Fernanda Heloisa [UNESP] (2009)
Supermarket plastic bags are produced by high density polyethylene (HDPE) and low density polyethylene (LDPE) resins. In Brazil, are produced annually around 150 plastic bags per capita. Disposed in landfills, the supermarket plastic bags prevent the passage of water by slowing the breakdown of biodegradable materials and hindering compaction of waste, according to their low degradability. This work investigated the biodegradation of PE bags containing additive oxo-biodegradable and bags without additives: buried in soil columns, exposed in a controlled environment and exposed to air. The analysis methods used to assess the changes brought in the bags with respect to microbial action and exposure time were weight loss, thickness measurement, infrared (FTIR), scanning electron microscopy (SEM) and contact angle. The results showed that the use of prodegradant agents such as oxobiodegradable additives in polyethylene bags, buried in soil for 270 days, was not efficient to accelerate the biodegradation by microorganisms. It seems that these additives have been more efficient to degrade the colored pigmentation of printed bags, under the influence of light and heat.